Miniature hybrid plasma focus extreme ultraviolet source driven by 10 kA fast current pulse - Mohanty, S. R.; Sakamoto, T.; Kobayashi, Y.; Song, I.; Watanabe, M.; Kawamura, T.; Okino, A.; Horioka, K.; Hotta, E. (Review of scientific instruments, 2006)
A miniature hybrid plasma focus device, operated in xenon gas medium and driven by a 10 kA fast current pulse, has been used to generate extreme ultraviolet radiation in the range of 6 – 15 nm . At present the radiation characteristics from xenon plasma were mainly assessed qualitatively using standard tools such as visible light framing camera, extreme ultraviolet (EUV) pinhole camera, and EUV photodiode. Strong pinching of xenon plasma is indicative from both visible and EUV imagings. The maximum size of the EUV emitting zone is estimated to be of the order of 0.21 × 1.55 mm and the estimated value is within the accepted value as benchmarked by industries. The EUV intensity measurement by photodiode showed fairly isotropic radiation at least in a half solid angle. This device can be developed further as a competent source for EUV metrology or lithography applications.